2013
DOI: 10.1111/jace.12453
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Computer‐Aided Molecular Design (CAMD) Using the Signature Molecular Descriptor—Part 1. Identification of Surface Tension Reducing Agents and the Search for Shrinkage Reducing Admixtures

Abstract: The development of new admixtures for concrete is normally an experimental endeavor in that the molecular scaffolds of existing admixtures are modified and tested. This approach is time consuming, incremental and typically expensive. Alternatively, a computer‐aided molecular design (CAMD) approach is proposed that uses the Signature molecular descriptor. CAMD is the application of computer‐implemented algorithms that are utilized to design molecules with optimally predicted properties such that they can be tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…It should be noted that the pipeline correlates structural feature patterns in compounds with experimental data and applies those correlations, in the form of models, to find new potential ligands. It is not equipped to identify why specific ligands are biologically active while others are not, though speculations can be drawn by correlating atomic Signature to model coefficients as was done in prior work [ 79 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the pipeline correlates structural feature patterns in compounds with experimental data and applies those correlations, in the form of models, to find new potential ligands. It is not equipped to identify why specific ligands are biologically active while others are not, though speculations can be drawn by correlating atomic Signature to model coefficients as was done in prior work [ 79 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to streamline and accelerate the discovery of admixture molecules, Kayello et al . and Shlonimskaya et al .…”
Section: Reviewsmentioning
confidence: 99%
“…Some applications of ML to cementitious materials and related chemical admixtures have been made already, and they provide a glimpse of the latent power and flexibility of such methods for designing cementitious composites when sufficient training data are available. Phase segmentation of cement powder microstructures is now routinely accomplished by unsupervised ML, using clustering algorithms trained on subsets of 2D backscattered electron micrographs and X‐ray microanalysis data of polished cement powder cross sections .…”
Section: Reviewsmentioning
confidence: 99%
“…Thus, surface tension reduction of pore water is the controlling factor for shrinkage mitigation . However, most studies looked at surface tension reduction of SRas in pure water, whereas, few have considered pore solution …”
Section: Introductionmentioning
confidence: 99%
“…Kayello et al (2014) recently demonstrated a Computer‐Aided Molecular Design (CAMD) method using an inverse‐quantitative structure property relationship (I‐QSPR) approach to identify new SRas. They found that glycol ether acetate compounds have shrinkage reducing capacity and have less adverse effects on compressive strength . Glycol ether acetate compounds, thus, appear to be a new class of SRa that may biodegrade more readily than some current commercial SRA compounds and retain early age strength.…”
Section: Introductionmentioning
confidence: 99%